Penyuluhan Pengajuan Pinjaman KUR bagi Para Pedagang di Sekitar Kampus Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta - Setiawan, Desy Amaliati; Wasif, Said Khaerul; Yusuf, Muhammad; Diana, Apry Linda; Husen, Irfan Arif; Noormansyah, Irvan (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2024)
Many MSME (Micro, Small, and Medium Enterprises) entrepreneurs face difficulties in obtaining capital to run their businesses. This activity aims to provide counseling on how to apply for the People's Business Credit (KUR) for traders around the campus of the Sekolah Tinggi Ilmu Ekonomi Indonesia in Jakarta. The community service was conducted at the Campus C Postgraduate School of Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta on Thursday, May 9, 2024. The results of this activity showed an increase in traders' knowledge regarding capital, sales turnover, and profits. This program, which involves the provision of KUR loans, has a significant impact on increasing the income of traders, enabling them to develop their businesses and improve their economic welfare.